Perubahan Berat Badan Bayi Usia 6-12 Bulan Sebelum dan Sesudah Mendapat Baby Spa - Mulyana, Intan; Setyaningsih, Wahyu (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2020)
The first 1000 days of life are critical times in the child's growth and development stage. Nutrition and stimulation received by infants have a long-term impact on life during adulthood. Baby spa is a form of stimulation that combines baby massage and swimming which has many benefits for babies. The purpose of this study was to determine changes in body weight of infants aged 6-12 months before and after getting a baby spa. The design of the study was comparative analytic, with a prospective approach. The study population of 35 infants using accidental sampling technique obtained a sample of 32 infants aged 6-12 months who met the inclusion criteria. The research instrument used baby weight scales. Data analysis using paired t test. The results showed that there was a change in body weight of infants aged 6-12 months before and after receiving a baby spa with an average body weight before baby spa 8092.19 grams to 8673.44 grams after 2 treatments (p value <0.001). Baby spas can increase vagus nerve tone (10th brain nerve) which causes an increase in the levels of the enzyme absorption of gastrin and insulin, so that food absorption will be better and can increase the baby's weight. A baby spa with regular frequency is needed to maximize the growth and development of the baby. Keywords: Baby Weight, Baby Spa